COVID-19 Era Effect on Pandemic and Post-pandemic Pediatric Telemedicine Use: A Survey of the European Academy of Pediatrics Research in Ambulatory Settings Network - Reingold, Stephen M.; Hadjipanayis, Adamos; van Esso, Diego; del Torso, Stefano; Dornbusch, Hans Jürgen; de Guchtenaere, Ann; Pancheva, Rouzha; Mujkic, Aida; Syridou, Garyfallia; Valiulis, Arunas; Mazur, Artur; Rios, Joana; et al. (Frontiers in Pediatrics, 2021)
BACKGROUND: During the COVID-19 pandemic, telemedicine use has increased within community pediatrics. This trend runs counter to reluctance to adaptation of the new mode of healthcare that existed prior to the pandemic. Little is known about what we can expect after the pandemic: if physicians will opt for telemedicine modalities and if tele-pediatrics will continue to be a significant mode of community pediatric care. OBJECTIVE: The goal of this study was to survey primary pediatric care providers as to their experiences and clinical decision making with telemedicine modalities prior to and during the COVID-19 pandemic, as well as their projected use after the pandemic ends. MATERIAL AND METHODS: Using the EAPRASnet database we surveyed pediatricians throughout Europe, using a web-based questionnaire. The survey was performed during the COVID-19 pandemic (June-July 2020), assessed telemedicine use for several modalities, prior to and during the pandemic as well as predicted use after the pandemic will have resolved. Participants were also surveyed regarding clinical decision making in 2 hypothetical clinical scenarios managed by telemedicine. RESULTS: A total of 710 physicians participated, 76% were pediatricians. The percentage of respondents who reported daily use for at least 50% of all encounters via telemedicine modalities increased during the pandemic: phone calls (4% prior to the pandemic to 52% during the pandemic), emails (2% to 9%), text messages (1% to 6%), social media (3% to 11%), cell-phone pictures/video (1% to 9%), and video conferencing (1% to 7%) (p<0.005). The predicted post-pandemic use of these modalities partially declined to 19%, 4%, 3%, 6%, 9%, and 4% respectively (p<0.005), yet demonstrating a prospectively sustained use of pictures/videos after the pandemic. Reported high likelihood of remotely treating suspected pneumonia and acute otitis media with antibiotics decreased from 8% and 16% during the pandemic to an assumed 2% and 4% after the pandemic, respectively (p <0.005). CONCLUSIONS: This study demonstrates an increased utilization of telemedicine by pediatric providers during the COVID-19 pandemic, as well as a partially sustained effect that will promote telemedicine use as part of a hybrid care provision after the pandemic will have resolved.